SYNTHESIS, CHARACTERIZATION, ANTICANCER, ANTIBACTERIAL AND ANTIOXIDANT EVALUATION OF MACROCYCLIC COPPER (II) COMPLEXES DERIVED FROM THIOSEMICARBAZIDE. - BRAJRAJ SHARMA; RICHA KOTHARI (International Journal of Pharma and Bio Sciences, 2015)
Three Cu (II) complexes were prepared from N4 substituted thiosemicarbazones [Cu (p-clbhtsc)2]Cl2.2H2O [1], [Cu (p-mbhtsc)2 ]Cl2. 2H2O [2] and [Cu (p-nbhtsc)2]Cl2.2H2O [3], where (p-clbhtsc) = para-chloro benzaldehyde thiosemicarbazone , (p-mbhhtsc) = p-methoxy benzaldehyde thiosemicarbazone, (p-nbhtsc) = para-nitro benzaldehyde thiosemicarbazone; have been synthesized and characterized by elemental analysis, IR, H1NMR, 13CNMR, LC-MS, and electronic spectra. The magnetic moments and electronic spectral studies suggest distorted octahedral geometry for all Cu (II) complexes. The cytotoxicity activity against breast cancer cell lines MCF-7, antibacterial and antioxidant activities were evaluated for all the above compounds. The synthesized compounds were screened for their in vitro antibacterial activity using Disc Diffusion method against various strains of gram negative and gram positive bacteria. Tetracyclin was used as standard drug in the test. All these macrocyclic Cu (II) complexes evaluate their superoxide dismutase activity to scavenge the superoxide anions generated by the DPPH and ferric oxide oxidase system.